Harmonics Analysis and Calculation in Power System Networks - Mohammed k.edan (Engineering and Technology Journal, 2008)
Abstract- The harmonic distortion in the power system is increasing with wide use ofnonlinear loads such as wave rectifiers, static VAR compensator, and solid-state controlleddevices.Thus, it is important to analyze and evaluate the various harmonic problems in thepower system prior to their occurrence. This paper presents a technique to analyzepropagation of harmonic current and voltage in power system networks, and determine thelocation and magnitude of the maximum harmonic current and voltage in the network.Frequency dependent models of a power system elements and loads have been developedfor the appropriate range of frequency. The harmonic source representation is described.The location of harmonic source, and the system loads are all found to be factors indetermining the magnitude of harmonic currents and voltages flow in the system.